The Effect of Squat Jump Training on Improving Lower-Body Muscle Power in Volleyball Players from the LBT Bengkulu Selatan Club - Richard Chalief Akbar; Dody Ertanto; Mariska Febrianti (UNIVED Press, Universitas Dehasen Bengkulu, 2026)
This study aims to determine the effect of squat jump training on improving lower-body explosive strength in volleyball players from the LBT Bengkulu Selatan Club. A total sampling method was used to determine the number of respondents, resulting in 12 volleyball athletes from the LBT Bengkulu Selatan Club. This experimental study employed a One-Group Pre-test–Post-test design, a pre-experimental design that includes a pre-test (test before treatment) and a post-test (test after treatment) within a single group. Data collection was conducted using test scores. Descriptive data analysis and the t-test were used. The results of this study indicate that squat jumps have an effect on improving the lower limb muscle power of volleyball players at the LBT Bengkulu Selatan Club, with a calculated t-value of 3.281 and a critical t-value of 2.201 at a significance level of α = 0.05 and df = 12.